Integrasi Modul Fitur Untuk Manajemen Daya Listrik Pada Sistem Informasi Keuangan (SIK) - Nur Fahrurozi; Handrie Noprisson (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
This study aimed to develop a web-based application module to monitor electricity consumption on network devices at PT. LinkNet, an internet service provider. The main issue faced was internet service disruptions caused by the depletion of electricity credit on prepaid meters, which could result in network devices losing power. To address this, a prepaid electricity monitoring module was developed to estimate the time until the credit runs out and prevent service disruptions. The methodology used in this research was the waterfall software development model, which included stages such as literature review, problem identification, data collection, application design and testing, and reporting the test results. The results indicated that the application helped users monitor electricity consumption in real-time, display the estimated time until the electricity credit expired, and provide downloadable usage reports. The application could be used for electricity management and minimizing the potential for internet service disruptions caused by electricity usage management issues.